Overactive NF-KB signaling as a druggable target and evaluation of parthenolide an NF-KB inhibitor in canine cancer - Schlein, Lisa Janelle, author; Thamm, Douglas H., advisor; Avery, Paul, committee member; Duval, Dawn, committee member; MacNeill, Amy, committee member (Colorado State University. Libraries, 2022)
This study provides a unique translational research opportunity to help both humans and dogs diagnosed with diseases that carry dismal prognoses in both species: histiocytic sarcoma (HS), hemangiosarcoma (HSA), and disseminated mastocytosis (MCT). Lymphoma is one of the most common cancer types affecting dogs and humans, and therefore, novel therapeutic approaches are always needed. For all of these cancer types, dogs and human cancers share common molecular abnormalities, consistent with a conserved pathogenesis between species. Relative to traditional murine models for human cancers, dogs are genetically diverse, large mammals with heterogeneous, spontaneous tumors. Dogs generally receive good medical care and share the environmental factors with humans, and accordingly, dogs with spontaneous tumors are an excellent model for human oncology generally. Additionally, although disseminated HS, MCT and visceral HSA are exceedingly rare diseases in humans, they are more common in some dog breeds, giving us the opportunity to study this disease in a larger population than would otherwise be available. Therapeutics evaluated in dogs with these diseases stand to benefit both canine and human patients. NF-kB proteins are a family of structurally related, eukaryotic transcription factors that have 400+ genetic targets, and are involved in many vital cellular processes, including innate immunity, inflammatory responses, development, cellular growth, and survival. Not surprisingly, overactivation of NF-kB is a feature of many chronic disease processes, including cardiac disease, neurodegenerative disease, immune-mediated disease, and cancer. While NF-kB overactivation has been documented extensively in human oncology, there is a relative paucity of data documenting the same phenomenon in veterinary medicine. As part of this study, large scale validation of NF-kB overactivation was performed in canine cancer via immunohistochemistry of 215 tumor samples (lymphoma, HS, HSA, and MCT). Antibodies were validated for use via western blot, immortalized cell pellets, and evaluation of normal canine tissues. In addition to validation of NF-kB overactivation, assays were performed to assess the therapeutic potential of parthenolide (PTL), a known, canonical NF-kB signaling inhibitor with additional mechanisms of antineoplastic activity, including alteration of cellular redox balance. Growth inhibition assays were performed with canine cell lines and primary lymphoma cells isolated from canine patients, using PTL alone or in combination with redox-perturbing standard-of-care therapeutics. Cell death was assessed using flow cytometry. Immunofluorescence was used to assess NF-kB localization, western blot was used to assess NF-kB activity with and without PTL, and canine cells were transfected with a reporter gene cassette containing the NFkB consensus sequence followed by firefly luciferase gene to study the effect of PTL on NF-kB-related luminescence. PTL's effects on glutathione and reactive oxygen species generation were assessed with a colorimetric assay and a fluorescent H2DCFDA assay, respectively. Genetic expression changes were assessed with RNA sequencing of HS cells, with and without PTL treatment. A mouse model of disseminated HS was created with NF-kB luminescent cells to study the effect of PTL on this disease in vivo. Many spontaneous canine tumor samples have nuclear p65 and p100/p52 IHC staining that is of greater magnitude than observed in comparable, normal cell populations, indicating the promise of PTL and other therapeutics that target aberrant NF-kB signaling. Canine cell lines and primary cells are sensitive to PTL and undergo dose-dependent apoptosis following exposure to drug. PTL exposure also leads to glutathione depletion, reactive oxygen species generation, and NF-kB inhibition in canine cells. Standard-of-care therapeutics broadly synergize with PTL. In two canine HS cell lines, genetic expression of NF-kB pathway signaling partners is downregulated with PTL therapy. Preliminary data suggest that PTL inhibits NF-kB activity of cells in a mouse model of disseminated HS. Overall, these data support further investigation of compounds that can antagonize canonical and alternative NF-kB pathway signaling, which are overactivated in canine lymphoma, HS, HSA, and MCT disease. PTL is one promising therapeutic that acts, in part, via canonical NF-kB antagonism in canine neoplasms. Further investigation of this compound in vivo is underway in a mouse model of disseminated HS, and if this study is successful, it will provide strong justification for clinical trials with this compound in dogs.